Toxic trace element contents in gluten-free cereal bars marketed in Argentina - Hidalgo, Melisa Jazmín (2015)
Fil: Hidalgo, Melisa Jazmín. Universidad Nacional del Nordeste. Facultad de Ciencias Exactas y Naturales y Agrimensura; Argentina.